Development of dribbling in talented youth soccer players aged 12-19 years: A longitudinal study - Huijgen, B. C. H.; Elferink-Gemser, M. T.; Post, W.; Visscher, C. (Journal of Sports Sciences, 2010)
The aims of the current study were to assess the development and determine the underlying mechanisms of sprinting and dribbling needed to compete at the highest level in youth soccer. Talented soccer players aged 12-19 years (n = 267) were measured on a yearly basis in a longitudinal study over 7 years, resulting in 519 measurements. Two field tests, the Shuttle Sprint and Dribble Test and the Slalom Sprint and Dribble Test, were assessed. Anthropometric characteristics, years of soccer experience, and duration of practice were recorded. The longitudinal data were analysed with multi-level modelling. Comparing the two tests at baseline, low correlations were observed (sprinting: r = 0.49; dribbling: r = 0.22), indicating that each test measures distinct qualities (acceleration vs. agility). Low-to-moderate correlations were found between dribbling and sprinting within each test (Shuttle Sprint and Dribble Test: r = 0.54; Slalom Sprint and Dribble Test: r = 0.38). Both dribbling and sprinting improved with age, especially from ages 12 to 14, but the tempo of development was different. From ages 14 to 16, sprinting improved rapidly in contrast to dribbling; this was especially evident on the Slalom Sprint and Dribble Test. In contrast, after age 16 dribbling improved considerably but sprinting hardly improved. Besides age, the factors that contribute to dribbling performance are lean body mass, hours of practice, and playing position.